2010
DOI: 10.1351/pac-con-09-11-05
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic-based modeling on a micro-scale atmospheric-pressure plasma jet

Abstract: Diagnostic-based modeling (DBM) actively combines complementary advantages of numerical plasma simulations and relatively simple optical emission spectroscopy (OES). DBM is applied to determine spatial absolute atomic oxygen ground-state density profiles in a micro atmospheric-pressure plasma jet operated in He-O 2 . A 1D fluid model with semi-kinetic treatment of the electrons yields detailed information on the electron dynamics and the corresponding spatio-temporal electron energy distribution function. Benc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…For the description of spatial distributions of the generated reactive species, 1D (onedimensional) or 2D models are used. In [102,112,120] the simulation of RF discharges between the parallel-plate electrodes in a transverse gas flow is performed using a 1D model (assuming that the variation of the discharge parameters along the flow is negligible). The balance equations for the reactive species j are: ,…”
Section: Brief Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…For the description of spatial distributions of the generated reactive species, 1D (onedimensional) or 2D models are used. In [102,112,120] the simulation of RF discharges between the parallel-plate electrodes in a transverse gas flow is performed using a 1D model (assuming that the variation of the discharge parameters along the flow is negligible). The balance equations for the reactive species j are: ,…”
Section: Brief Historical Perspectivementioning
confidence: 99%
“…While two-photon laser induced spectroscopy yields reliable density results of atomic oxygen (see above), this technique is complex and requires access for the laser beam and the observation optics. The DBM combines one-dimensional numerical simulation based on fluid equations with kinetic treatment of the electrons [120,209,210].…”
Section: Combination Of Optical Emission Spectroscopy and Modellingmentioning
confidence: 99%
“…The jet is operated in helium at various flow rates from 200 sccm to 5 slm. The electric field between the electrodes causes a breakdown in the gas and produces a plasma with electron temperatures and densities of about 1 to 2 eV and 10 10 cm −3 , respectively [7,8]. Atoms and molecules in the feed gas become excited, dissociated or ionized by electron impacts.…”
Section: The Atmospheric Pressure Micro-plasma Jetmentioning
confidence: 99%
“…When operated into the ambient air, the reactive plasma effluent activates the neutral oxygen and nitrogen species generating a rich mixture of RONS [8][9][10][11][12]; these are subsequently delivered to the biological target by the plasma and gas flow. Atmospheric-pressure, molecular beam mass spectrometric studies have revealed secondary reactive species including tens of positively charged species and hundreds of negatively charged species and neutrals are generated by the interaction between the APPJ and / or APPJ effluent (primary species e.g.…”
Section: Introductionmentioning
confidence: 99%